Expression and purification of adhesive recombinant proteins, sericin 2 and salivary gland secretion 3 - Vu, Trang Thanh (Jihočeská univerzita, 2020)
Recombinant proteins derived from Bombyx mori Ser-2 gene and Drosophila melanogaster Sgs3 gene were expressed in bacterial expression systems, purified and partially characterised. The identity of the expressed recombinant proteins was verified by mass spectroscopy. The recombinant proteins were tested for their ability to coat hydrophobic surfaces and sequentially serve as a substrate for the attachment of cells in tissue culture. The quality of the recombinant protein surface coating was examined by scanning electron microscopy. The results show that further optimisation for the purification, solubilization and refolding of these recombinant proteins is needed to incorporate their potential as biomaterials in the future.
Expression and purification of adhesive recombinant proteins, sericin 2 and salivary gland secretion 3
Keywords: proteins; recombinant; expression; bombyx; drosophila; proteins; recombinant; expression; bombyx; drosophila